Thermally controlling the singlet-triplet energy gap of a diradical in the solid state - Su, Yuanting; Wang, Xingyong; Wang, Lei; Zhang, Zaichao; Wang, Xinping; Song, You; Power, Philip P (Chemical science (Cambridge), 2016)
Diradicals, molecules with two unpaired electrons, are reactive intermediates that play an important role in many fields. Their defining feature is the energy difference between their singlet and triplet states, which provides direct information on the extent of their electron exchange interactions. Such knowledge is essential for understanding their diradical character, which is controllable internally by modification of the electronic and steric properties of the substituents. We now report that the energy gap of a diradical in the solid state can also be controlled by an external stimulus. The dication diradical of 4,4′′-di(bisphenylamino)- p -terphenyl exhibits two singlet states with different exchange coupling constants at different temperatures as determined by SQUID and EPR measurements. The behavior is induced by the conformation change of the terphenyl bridge, the key structural unit of the species. The work presents an unprecedented instance of a thermally controllable singlet-triplet gap for a crystalline diradical and provides a novel diradical material relevant to the design of functional materials. Diradicals, molecules with two unpaired electrons, are reactive intermediates that play an important role in many fields.